2017
DOI: 10.1016/j.sjpain.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient experiences of a pain management centre: A qualitative study

Abstract: AbstractBackground and aimsTo improve care and management of patients with chronic pain it is important to understand patients’ experiences of treatment, and of the people and the environment involved. As chronic pain patients often have long relationships with medical clinics and pain management centres, the team and team interactions with the patients could impact the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
2
2
0
2
Order By: Relevance
“…The consideration of the impact of training lies within the broader literature and overall reports a positive correlation between increased training and positive experiences with service users. 4750 The current study highlights a similar relationship towards those with fibromyalgia. It supports further exploration into the impact of this training on facilitating attitudinal change.…”
Section: Discussionsupporting
confidence: 73%
“…The consideration of the impact of training lies within the broader literature and overall reports a positive correlation between increased training and positive experiences with service users. 4750 The current study highlights a similar relationship towards those with fibromyalgia. It supports further exploration into the impact of this training on facilitating attitudinal change.…”
Section: Discussionsupporting
confidence: 73%
“…Mittinty and colleagues similarly found that for patients with persistent pain, their most commonly stated positive experience of their treatment at a pain clinic was the support and validation staff provided for their condition. 19 Thus, this pilot study confirms a supportive physician-patient relationship is particularly important in the care and management of patients with persistent pain, where physician empathy and good understanding can assist patients with persistent pain to maintain a positive sense of wellbeing.…”
Section: Discussionsupporting
confidence: 66%
“…Similar feelings have been described by patients with other chronic pain conditions such as lumbar radiculopathy and neck pain, 16,21,44,51,52,55 all whom want confirmation their pain is real and to feel validated and reassured by their providers. 5,8,15,21,22,29,40,46,47,59,65 People living with chronic conditions, such as DCR, appear "healthy" with no visible symptoms to suggest they are unwell or suffering. This can lead to health care professionals being skeptical of their complaints and suggesting their pain is not attributable to a physical cause.…”
Section: Role Of Health Care Providers To Foster a Patientcentered Ap...mentioning
confidence: 99%